2013
DOI: 10.1177/0001699313496588
|View full text |Cite
|
Sign up to set email alerts
|

Do fixed-term and temporary agency workers feel socially excluded? Labour market integration and social well-being in Germany

Abstract: In this study we examine how employment insecurity affects social exclusion using data from the German panel study PASS. Assuming that secure employment is an important condition for the subjective feeling of social affiliation, we compare unemployed individuals and those in fixed-term, temporary agency or permanent employment. Applying hybrid random effects regression models we find that temporary workers feel less affiliated to society than permanent workers. This finding cannot be fully explained by economi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 32 publications
1
44
1
3
Order By: Relevance
“…Workers who (have to) accept peripheral jobs may face ''job discrimination'' in the sense that they get trapped in peripheral jobs, although they desire to work in core jobs (Elcioglu, 2010). TWA employment presents an exemplary case of peripheral employment: high job insecurity (Håkansson, Isidorsson, & Kantelius, 2012;Hall, 2006;Olofsdotter, 2012;Silla, Gracia, & Peiro, 2005), low wages and few benefits (Elcioglu, 2010;Jahn & Pozzoli, 2013;Kojima, 2015), unpredictable or irregular schedules (Aletraris, 2010;Håkansson, Isidorsson, & Strauss-Raats, 2013;Kalleberg, Reskin, & Hudson, 2000), little training and poor employability (Håkansson et al, 2013;Knox, 2010), and poor social relations at work (Forde & Slater, 2006;Gundert & Hohendanner, 2014;Winkler & Mahmood, 2015). Moreover, a general characteristic that increases the vulnerability of TWA workers is the triadic employment relationship: they have to deal with both a ''de juro'' employer (the temporary employment agency) and a ''de facto'' employer (the client-company), whereas other employees are only bound to one single employer (Aletraris, 2010;Underhill & Quinlan, 2011).…”
Section: Established-outsider Relations In the Context Of Temporary Amentioning
confidence: 99%
“…Workers who (have to) accept peripheral jobs may face ''job discrimination'' in the sense that they get trapped in peripheral jobs, although they desire to work in core jobs (Elcioglu, 2010). TWA employment presents an exemplary case of peripheral employment: high job insecurity (Håkansson, Isidorsson, & Kantelius, 2012;Hall, 2006;Olofsdotter, 2012;Silla, Gracia, & Peiro, 2005), low wages and few benefits (Elcioglu, 2010;Jahn & Pozzoli, 2013;Kojima, 2015), unpredictable or irregular schedules (Aletraris, 2010;Håkansson, Isidorsson, & Strauss-Raats, 2013;Kalleberg, Reskin, & Hudson, 2000), little training and poor employability (Håkansson et al, 2013;Knox, 2010), and poor social relations at work (Forde & Slater, 2006;Gundert & Hohendanner, 2014;Winkler & Mahmood, 2015). Moreover, a general characteristic that increases the vulnerability of TWA workers is the triadic employment relationship: they have to deal with both a ''de juro'' employer (the temporary employment agency) and a ''de facto'' employer (the client-company), whereas other employees are only bound to one single employer (Aletraris, 2010;Underhill & Quinlan, 2011).…”
Section: Established-outsider Relations In the Context Of Temporary Amentioning
confidence: 99%
“…15 The temporary agency workers are thus in many ways on the fringe of society, with a lower standard of living than their colleagues, the trend noticed across many countries. For example, Gundert and Hohendanner (2014) found that in Germany temporary workers felt less affiliated to society than permanent workers.…”
Section: A Segmented Labor Marketmentioning
confidence: 99%
“…Compared with standard employment, contingent work is characterized by reduced job security (Giesecke, 2009), lower wages (Berlinski, 2008;Gebel, 2009;Dube and Kaplan, 2010;Goldschmidt and Schmieder, 2017), worse career prospects (Giesecke and Groß, 2003;Gebel, 2009), higher perceptions of social exclusion (Gundert and Hohendanner, 2014) and stronger demands for redistribution (Marx, 2014).…”
Section: The Feedback Effect Of Subcontracting: Mechanisms and Competmentioning
confidence: 99%